Material compatibility of ORC working fluids with polymers. (September 2017) - Eyerer, Sebastian; Eyerer, Peter; Eicheldinger, Markus; Sax, Sebastian; Wieland, Christoph; Spliethoff, Hartmut
Abstract: In this study, the material compatibility of refrigerants focusing on hydrofluoroolefines (HFO) with typical polymers in ORC plants and refrigeration units is analyzed with consistent testing conditions and a complete uncertainty analysis of the results. One state-of-the-art refrigerant, namely R245fa, as well as the low-GWP fluids R1233zd-E and R1234yf are taken into account. The investigated polymers are ethylene-propylene-diene rubber (EPDM), fluoric rubber (FKM) and polytetrafluoroethylene (PTFE). In the case of EPDM, two different compositions are analyzed. To complement the study the material compatibility with a polyolester (POE) lubricant is also investigated. The material compatibility is evaluated by changes in volume, weight, Shore A as well as in small load hardness. With the small load hardness measurements, the hardness directly at the samples surface can be determined and thus important information on chemical interaction is provided. This study points out the importance of material compatibility testing especially investigating the difference between hydrofluorocarbons (HFC) and HFO, because the unsaturated characteristic of the HFO may lead to considerable changes in material compatibility compared to HFC refrigerants.